Anstoss Berlin : Kunst macht Welt = Art makes the world - Haus am Waldsee, Berlin (Berlin : Haus am Waldsee Berlin, 2006)
Ackermann, Franz ; Bisky, Norbert ; Bock, John ; Breitz, Candice ; De Broin, Michel ; Bulloch, Angela ; Cardiff, Janet ; Bures Miller, George ; Dahlem, Björn ; Dean, Tacita ; van Eeden, Marcel ; Eliasson, Olafur ; Eller, Thomas ; Elmgreen & Dragset ; Erkmen, Ayse ; Faithfull, Simon ; Favre, Valérie ; Florschuetz, Thomas ; Fricke, Adib ; Frize, Bernard ; Garenne, Christine de la ; Grosse, Katharina ; Gröting, Asta ; Guagilardi, Carla ; Hatoum, Mona ; Havekost, Eberhard ; Haygarth, Stuart ; Heger, Swetlana ; Herrera, Arturo ; Jenssen, Olav Christopher ; Koganezawa, Takehito ; Krauss, Clemens ; Lewandowsky, Via ; Locher, Thomas ; Lucander, Robert ; Manchot, Melanie ; Markowitsch, Rémy ; Meese, Jonathan ; Melhus, Bjorn ; Monk, Jonathan ; Morrison, Joel ; Nitsche, Frank ; Pernice, Manfred ; Pflumm, Daniel ; Pousttchi, Bettina ; Yufen, Qin ; Rentmeister, Thomas ; Rockenschaub, Gerwald ; Rothschild, Miguel ; Sala, Anri ; Sander, Karin ; Schäfer, Albrecht ; Shimabuku ; Sehgal, Tino ; Sidén, Ann-Sofi ; Sixay, Markus ; Siotawa, Florian ; Tiravanija, Rirkrit ; Velten, Till ; Wang Fu ; Wasmuth, Corinne ; Welz, Peter
Exhibition "Anstoss Berlin - Kunst macht Welt = Art makes the world", Berlin, Haus am Waldsee, 22.06.2006 - 17.09.2006
Duits
boek